Impacts of Adaptive Fire Management on Forest Structure and Regeneration: A Case Study from Ban Pak Thab Community Forest, Uttaradit Province, Thailand - Podong, Chattanong; Mhon-ing, Sukanya (Jurnal Manajemen Hutan Tropika, 2026)
There is an urgent need for innovative approaches to forest management given the increasing incidence and intensity of wildfire due to climate change. The impact of interacting prescribed burning, fuel reduction and natural fires on tree structure in Ban Pak Thap community forest; Thailand Twelve, 40 × 40 m, experimental plots were studied for the ecological effects of four different management practices. The findings demonstrate that, not only do prescribed burning and fuel treatments significantly improve forest regeneration by decreasing inter-tree competition, enhancing nutrient recycling and encouraging superior sapling growth but also they also help to conserve species diversity as well as biomass accumulation. However, natural burning led to extensive reductions in tree density, species richness and total biomass. Extensive statistical analysis showed high relationships of the management practices tested on several ecological variables, and this demonstrated well the varying effects of these interventions. This result emphasizes the (compared to non-managed burns) advantageous effect of managed fire on other hand important information for sustainable development of management strategies concerning tropical forest ecosystems. This study highlights the potential benefit of adaptive management in reducing negative impacts of climate change on forest health and resilience.